A Retrospective Comparison of Older and Younger Adults Undergoing Early Laparoscopic Cholecystectomy for Mild to Moderate Calculous Cholecystitis. Issue 5 (6th May 2015) - Fuks, David; Duhaut, Pierre; Mauvais, Francois; Pocard, Marc; Haccart, Vincent; Paquet, Jean‐Christophe; Millat, Bertrand; Msika, Simon; Sielezneff, Igor; Scotté, Michel; Chatelain, Denis; Regimbeau, Jean Marc
<x xml:space="preserve">Abstract</x> Objectives To compare the demographic characteristics and intra‐ and postoperative outcomes in elderly adults (≥75) with those of younger adults undergoing early (<5 days after onset of complaints) cholecystectomy. Design Retrospective analysis from May 2010 to August 2012. Setting Randomized, multicenter, clinical trial (ABCAL Study, NCT01015417). Participants Individuals with mild or moderate acute calculous cholecystitis (ACC) according to the Tokyo Guidelines (N = 414; n = 78 aged 75–94, median 82; n = 336 aged 18–74, median 49). Measurements Demographic characteristics and pre‐, intra‐, and postoperative data. Results The elderly group was more likely to have an American Society of Anesthesiologists score of 3 or greater (62% vs 23%, P < .001), higher serum creatinine (103 vs 74 μmol/L, P < .001), and more‐severe ACC (moderate ACC (62% vs 50%, P = .05), gangrenous cholecystitis (38% vs 15%, P = .001)) on preoperative imaging and confirmed intraoperatively. Ulcerated mucosa (76% vs 61%, P = .001) was significantly more frequent in the elderly group. Operative time, postoperative mortality, and postoperative infectious (18% vs 14%, P = .35) and noninfectious (9% vs 3%, P = .80) complications were similar between the two groups. Median length of stay (7.0 vs 5.0 days, P = .54) and readmission rate (15% vs 4%, P = .07) were not significantly higher in the elderly group. No significant difference was observed for the subgroup of participants aged 80 and older. Conclusion In this randomized trial that included a selected sample of older adults, there was no difference in major outcomes between elderly adults and their younger counterparts after early cholecystectomy. The findings are limited because important geriatric outcomes such as delirium and functional decline were not examined.